PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN PENDEKATAN INKUIRI DI KELAS V SEKOLAH DASAR - Sari, Novia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research background by low learning results obtained by students in learning science in the classroom V SDN 02 Teratak Teleng Northern Bayang District. The purpose of this research is to improve student learning results in learning science using inquiry approaches. The research method used was Qualitative and Quantitative research through observation and final test. The results showed that learning science using inquiry approaches can improve learning results.   Kata kunci : pelaksanaan, hasil pembelajaran IPA